Work-Related Fatigue Among Inpatient Unit Nurses - Irman Somantri; Mia Yuliati; Peter Winwood; Dian Adiningsih (Journal of Nursing Care, 2020)
Nurse fatigue has been recognized as a threat to both nurse and patient safety. Comparing to other units, inpatient unit has lower nurse to patient ratio. Inpatient unit nurses also work in shift and experience shift rotation. Thus make them more vulnerable to experience fatigue. The purpose of this study was to describe work-related fatigue among inpatient unit nurses. A cross-sectional, descriptive design with cluster sampling technique was used to 93 staffs nurses in six wards. Work-related fatigue was measured using Occupational Fatigue Exhaustion Recovery (OFER) scale. The data were analyzed using descriptive statistics. A total of 93 nurses provided their personal information details and fully completed self-reported fatigue and recovery questionnaire. The mean (±SD) scores were 56.55 (±15.56), 42.83 (±19.46), and 51.07 (±16.98) for acute fatigue, chronic fatigue, and intershift recovery, respectively. Perinatology unit nurses had the highest acute and chronic fatigue and the lowest intershift recovery. Less experienced nurses experienced lower acute fatigue level which tends to increase progressively with increasing experience and accompanied by poorer recovery. Nursing administrators should consider individual factors while planning staff placement in order to optimize quality of care and meet the job demands in every different unit.